Reconfiguring Command Culture: Systematic Review on Organizational Dynamics and Leadership in the Military - Muchamad Andi Barata; Sari Dewi; Ing Kadir; Sarfilianty Anggiani; Deasy Aseanty (Owner : Riset dan Jurnal Akuntansi, 2025)
Military organizational culture plays a central role in shaping collective behavior, hierarchical structures, and leadership effectiveness. In the era of technological disruption and geopolitical complexity, military institutions encounter growing pressure to align traditional cultural values with leadership approaches that are more adaptive, transformative, and sustainable. This study seeks to explore the interplay between military organizational culture and leadership strategies, highlighting the challenges and opportunities for institutional transformation. The research employs a systematic literature review method, focusing on academic sources published within the last five years. Relevant studies were selected based on their emphasis on organizational dynamics, cultural adaptation, and leadership models in military institutions. The review process enabled the identification of prevailing themes and gaps that affect cultural and leadership integration. The results indicate that ambidextrous and transformational leadership approaches offer significant potential to strengthen flexibility, innovation, and operational effectiveness in military organizations. These approaches foster the ability to balance stability with adaptability in dynamic environments. However, findings also reveal persistent resistance to innovation and structural change, which slows the pace of cultural transformation and limits the effectiveness of leadership strategies. The discussion emphasizes the importance of embedding progressive values such as collaboration, innovation, and transparency into military culture and leadership development. Strengthening these values can reduce resistance and improve institutional capacity to adapt to future challenges. Ultimately, the study suggests that sustainable reform in military organizations requires an integrated approach that combines cultural renewal with leadership transformation.